2018
DOI: 10.31234/osf.io/9egbx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trait Self-Control and Self-Discipline: Structure, Validity, and Invariance Across National Groups

Abstract: The aim of the present study was to test the validity of the Brief Self-Control Scale (BSCS; Tangney, Baumeister and Boone 2004) including its dimensional structure based on competing one- and two-factor models, discriminant validity from the conceptually-related self-discipline construct, invariance across multiple samples from different national groups, and predictive validity with respect to health-related behaviors. Samples of undergraduate students (total N = 1282) from four national groups completed the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…One possibility is that self‐control and self‐discipline may be more related to behaviours where capacity for inhibition of impulsive responses is most salient, and industriousness and activity sub‐facets are more relevant to behaviours requiring sustained effort. This is consistent with recent work distinguishing between initiation and inhibition components of trait self‐control (Hagger et al., ; Maloney, Grawitch, & Barber, ; de Ridder, de Boer, Lugtig, Bakker, & van Hooft, ). We did not find evidence for this selective pattern of effects in our current study, but we did not adopt a multi‐component approach.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…One possibility is that self‐control and self‐discipline may be more related to behaviours where capacity for inhibition of impulsive responses is most salient, and industriousness and activity sub‐facets are more relevant to behaviours requiring sustained effort. This is consistent with recent work distinguishing between initiation and inhibition components of trait self‐control (Hagger et al., ; Maloney, Grawitch, & Barber, ; de Ridder, de Boer, Lugtig, Bakker, & van Hooft, ). We did not find evidence for this selective pattern of effects in our current study, but we did not adopt a multi‐component approach.…”
Section: Discussionsupporting
confidence: 92%
“…Although trait self‐control is also likely to be related to other sub‐facets such as industriousness and activity, research suggests that they may predict different behaviours. For example, the industriousness and activity facets have been shown to be uniquely related to the social cognition antecedents of physical activity and the behaviour itself (Hoyt et al., ; Vo & Bogg, ), while self‐discipline has been shown to be related to impulse‐related behaviours (Hagger et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students' trait self-control was measured using the 10-item Self-Discipline Scale (e.g., "I tend to carry out my plans") from the IPIP-HEXACO scales [66] with responses provided on four-point scales (1 = not like me at all and 4 = very much like me). Research has demonstrated the internal consistency and predictive validity of this scale in school contexts [67]. [64].…”
Section: Trait Self-controlmentioning
confidence: 99%